DESCRIPTION OF KNOWLEDGE ABOUT THE FULFILLMENT OF NUTRITION FOR SECURITY OFFICERS IN SHOPPING CENTERS MEGAMAS AREA - Dolfina Galela; Frangky William Mapanawang, Lieneke Tumbuan, Lidia Dusun, Juandi Lera (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
In the life of every human being, there must be a dream that is inseparable from the feeling of security and comfort in living their daily lives. A condition related to security is something that is needed by every human being who occupies a certain area. Apart from wanting security and comfort in living life, as a human being, of course, he also has basic needs in the form of primary needs, including clothing, food and shelter. To find out how to describe knowledge about fulfilling nutrition for security officers in shopping center Megamas Area Survey Research Methods with Purposive Sampling and conducting in-depth interviews. Security officers always pay attention to the intake of nutrients that enter the body considering this is very much needed in the guarding process in the midst of their duties and responsibilities. Knowledge of the fulfillment of proper nutrition for security officers who carry out their duties can have a positive influence on the performance of security officers.